1995
DOI: 10.1038/bjc.1995.332
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of glutathione S-transferase Mu (GSTM1) and susceptibility to malignant melanoma

Abstract: Summary The isoenzyme Mu of glutathione S-transferase (GSTM 1) is dominantly inherited, and the prevalence of this isoenzyme in the population is about 60%. The (Longstreth et al., 1992). As a host genetic factor, dysplastic naevi (DN), which are relatively distinct melanocytic lesions, can be precursors of melanoma, and responsible for the tendency of melanoma to run in families. Metabolic factors such as the isoenzyme Mu of glutathione S-transferase (GSTM1) should also be considered. GSTM1 has polymorphic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 13 publications
0
26
1
Order By: Relevance
“…Initial studies comparing melanoma cases with controls in the predominantly Anglo-Celtic populations of the United Kingdom and Australia found the same frequency (52%) of GSTM1 nullizygotes in both groups (Heagerty et al, 1994;Shanley et al, 1995) (Table 5). In contrast, there was a significantly increased frequency of GSTM1 null phenotype in melanoma cases compared with controls (58 versus 41%, P ¼ 0.002) from a Hospital-based study in Barcelona (Lafuente et al, 1995). The most noticeable feature of this study was the much lower frequency of nullizygotes in the Spanish controls compared to that observed in other Caucasian control populations.…”
Section: Gstm1contrasting
confidence: 43%
“…Initial studies comparing melanoma cases with controls in the predominantly Anglo-Celtic populations of the United Kingdom and Australia found the same frequency (52%) of GSTM1 nullizygotes in both groups (Heagerty et al, 1994;Shanley et al, 1995) (Table 5). In contrast, there was a significantly increased frequency of GSTM1 null phenotype in melanoma cases compared with controls (58 versus 41%, P ¼ 0.002) from a Hospital-based study in Barcelona (Lafuente et al, 1995). The most noticeable feature of this study was the much lower frequency of nullizygotes in the Spanish controls compared to that observed in other Caucasian control populations.…”
Section: Gstm1contrasting
confidence: 43%
“…1 Relatively little is known of the genetic factors that mediate susceptibility to and prognosis in sporadic CMM, although polymorphisms associated with the MCR1, 2,3 CDKN2A, 4 XRCC3 (DNA repair), 5 GSTM1, 6 vitamin D receptor, 7 cytochrome P-450 CYP2D6, 8 HLA-DQB1, 9,10 IL-10 11 and VEGF 12 genes may play some role in susceptibility to and/or prognosis in CMM. Accordingly, one report, 13 demonstrating a highly significant association between a functional SNP in the EGF gene (chromosome 4q25-q27) and both susceptibility to and invasive tumour Breslow thickness (as a marker of disease prognosis), is of note.…”
mentioning
confidence: 99%
“…The elevated expression of cytosolic GST in melanocytes is supposed to be engaged in detoxification of hazardous by-pro-ducts from melanin synthesis [32]. In line with this argumentation, humans with an inherent deficiency for GST expression are at higher risk to develop MM [33]. Regarding MM, several studies reported a high expression of the GST and a lower or lacking one of the isoforms ␣ and in tumor tissue as well as cell lines [34,35].…”
Section: Enzyme Systemsmentioning
confidence: 78%